Developing bait and lure-based integrated pest management module for mango fruit fly (Bactrocera dorsalis) management in Orissa - Singh, H S; Verghese, A; Stonehouse, J M; Mumford, J D; George, S; Naik, G; Pandey, V (The Indian Journal of Agricultural Sciences, 2008)
Experiments were conducted during 2003-06 in high density mango (Mangifera indica L.) orchards in Orissa to develop integrated pest management (IPM) module for fruit fly (Bactrocera dorsalis Hendel ) in mango. Three food baits and 5 substrates as carrier of methyl eugenol were evaluated to find out the most effective food bait and the best carrier to be used in BAT (bait application technique) and MAT (male annihilation technique), respectively. Jaggery was found better food bait, whereas plywood block was observed to be better carrier of methyl eugenol. The control and cost-effectiveness of male annihilation technique (50 mm x 50 mm x 12 mm) plywood blocks soaked in ethyl alcohol: methyl eugenol: malathion in the ratio of 6:4:1 for 48 hr and hung in branches @ 10/ha in bottle traps in 2 rounds) together with bait application technique (2 g carbaryl and 100 g jaggery in 1 litre water), supplemented with field sanitation was compared with the insecticide spray in the orchard. Male annihiliation technique and bait application technique together utilized 11.11 times less insecticide and 1.32 times less cost but resulted in nearly double protection (93-97%), as well as double cost: benefit ratio (1 : 21.76) than that of cover spray (53-56% and 1 : 10.9, respectively). Pesticide : produce ratio was 19.02 kg fruit/ml of insecticide, whereas only 1.14 in cover sprays. As such, the IPM module was field tested at constant level of male annihilation technique (2 rounds) and variable level of bait application technique (8, 6 and 4 rounds at 6, 8 and 12 days interval, respectively) in large area of mango plantation. Two rounds of male annihilation technique in conjunction with 6-8 rounds of bait application technique at 6-8 days interval supplemented with field sanitation can reduce fruit fly damage up to 87-95% in mango.